Rapid changes in rat pineal beta-adrenergic receptor: alterations in l-(3H)alprenolol binding and adenylate cyclase. - Kebabian, J W (1975)
The properties of the beta-adrenergic receptor which regulates adenylate cyclase [ATP pyrophosphate-lyase (cyclizing)8 EC 4.6.1.1] in the pineal gland are similar to the properties of the sites which specifically bind l-[3H]alprenolol, a potent beta-adrenergic antagonist. Stimulation of the beta-adrenergic receptor results in a 30-fold increase in the activity of N-acetyltransferase (= arylamine acetyltransferase; acetyl CoA:arylamine N-acetyltransferase, EC 2.3.1.5), an enzyme involved in the synthesis of thepineal hormone melatonin. In the normal diurnal light-dark cycle there is greater physiological stimulation of the beta-adrenergic receptor in the pineal during the night than during the day. Pineals from rats kept in constant light for 24 hr possess more hormone-sensitive adenylate cyclase and specifically bind more l-[3H]alprenolol than do pineals from rats kept in the dark overnight. When rats, exposed to light for 24 hr, are treated with the beat-adrenergic agonist isoproterenol, there is a rapid loss of both hormone-sensitive adenylate cyclase activity and specific l-[3H]alprenolol binding sites. There is no change in the affinity of adenylate cyclase for isoproterenol or for its substrate, ATP. Similarly, although there are fewer binding sites, there is no change in the affinity of the remaining sites for either agonist or antagonist. Inhibition of protein synthesis with cycloheximide does not affect the loss of either adenylate cyclase activity or specific binding sites. The data suggest that stimulation of the beta-adrenergic receptor causes a rapid decrease in the number of available receptors and in hormone-sensitive adenylate cyclase activity; conversely, lack of stimulation causes an increase in these parameters. It is suggested that these changes contribute to the phenomena of super- and subsensitivity in the pineal gland by regulating the capacity of the pineal to synthesize cyclic AMP in response to beta-adrenergic stimulation.